Advances in Alzheimer’s disease’s pharmacological treatment - Conti Filho, Carlos Elias; Loss, Lairane Bridi; Marcolongo-Pereira, Clairton; Rossoni Junior, Joamyr Victor; Barcelos, Rafael Mazioli; Chiarelli-Neto, Orlando; Silva, Bruno Spalenza da; Passamani Ambrosio, Roberta; Castro, Fernanda Cristina de Abreu Quintela; Teixeira, Sarah Fernandes; Mezzomo, Nathana Jamille (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD) is the most common type of dementia in elderly. Several hypotheses emerged from AD pathophysiology mechanisms. Although, no neuronal protective or regenerative drug is available nowadays. Researchers still work in drug development and finding new molecular targets to treat AD. Therefore, this study aimed to summarize main advances in AD pharmacological therapy. Clinical trials registered in The National Library of Medicine database were selected and analyzed accordingly to molecular targets, therapeutic effects and safety profile. The most common outcome was lack of efficacy. Only seven trials concluded that tested drugs were safe and induced any type therapeutic improvement. Three works showed therapeutic effects followed by toxicity. Besides aducanumab recent FDA approval, antibodies against amyloid-β (Aβ) showed no noteworthy results. 5-HT6 antagonists, tau inhibitors and nicotinic agonists data were discouraging. Although, anti-Aβ vaccine, BACE inhibitor and anti-neuroinflammation drugs showed promising results.